Polysaccharides of Sporoderm-Broken Spore of Ganoderma lucidum Modulate Adaptive Immune Function via Gut Microbiota Regulation. (23rd March 2021) - Su, Lu; Li, Dan; Su, Jiyan; Zhang, Enqi; Chen, Shaodan; Zheng, Chaoqun; Luo, Ting; Li, Muxia; Chen, Xiaohong; Huang, Guoxin; Xie, Yizhen; Li, Shanshan
Abstract : Ganoderma lucidum (Leyss.Fr.) Karst is one of the well-known medicinal macrofungi all over the world, and mounting researches have focused on the polysaccharides derived from the spores of G. lucidum . In the present study, BALB/c mice ( n  = 8–10) were administered with crude polysaccharides of G. lucidum spores (CPGS) and the refined polysaccharides of G. lucidum spores (RPGS) for 30 days to investigate their effect on the adaptive immune system. Results showed that CPGS and RPGS displayed diverse effects on the lymphocyte activity in the spleen. The splenocyte proliferation activity upon mitogen was suppressed by CPGS and RPGS, while the NK cell's tumor-killing ability was promoted by CPGS. Both CPGS and RPGS could increase the proportion of naïve T cells in thymus, but only RPGS significantly uplifted the percentage of T cells, as well as the T cell subsets, in peripheral blood, and promoted the activation by upregulating the expression of costimulatory factor CD28. Moreover, 16S sequencing results showed that the effects of CPGS and RPGS were closely related to the regulation of gut microbiota. β -diversity of the microbiome was evidently changed by CPGS and RPGS. The phytoestrogen/polysaccharide-metabolizing bacteria ( Adlercreutzia, Parabacteroides, and Prevotella ), and an unclassified Desulfovibrionaceae, were remarkably enriched by CPGS or RPGS, and functions involving carbohydrate metabolism, membrane transport, and lipid metabolism were regulated. Moreover, the enrichments of Adlercreutzia, Prevotella, and Desulfovibrionaceae were positively related to the immune regulation by CPGS and RPGS, while that of Parabacteroides displayed a negative correlation. These findings suggested a promising effect of the polysaccharide from sporoderm-broken spore of G. lucidum in immune regulation to promote health control.